2005-06 Farm Bill Survey: Florida Producer Views on Conservation and Environmental, Trade, and Food System and Regulatory Policies - Rodney L. Clouser (EDIS)
FE665, a 5-page report by Rodney L. Clouser, is one of four fact sheets reporting information collected from Florida producers concerning attitudes and views regarding U.S. Congressional enactment of the next farm bill. This fact sheet focuses on questions of conservation and environmental, trade, food system and regulatory policies asked of Florida farm producers. Published by the UF Department of Food and Resource Economics, October 2006.